Analytical and rheological studies of modified gel dosimeters exposed to X-ray beams - Romero, Marcelo Ricardo (2016)
The need to know the dose of X-rays to be applied to patients suffering diseases such as cancer requires accurate and stable dosimetric devices. Currently, the use of gelatin-based dosimeters has yielded excellent results but lack adequate thermal stability. In this paper a chemical modification of the gelatin (at concentrations typically used for the preparation of dosimeters) using glutaraldehyde as a cross-linking agent is proposed. Through rheological studies it was found that modified gelatin with glutaraldehyde concentrations between 0.15 and 0.50% w/v shows better thermal stability with an increase in elastic modulus of up to 100 times at 37 °C and convenient reaction times for the preparation of the dosimeters. Subsequently, a mathematical model to easily predict the elastic modulus of materials prepared with different concentrations of gelatin and glutaraldehyde was proposed. The analytical response of modified and unmodified materials was evaluated and no significant alteration of the dosimetric sensitivity was found in the dosimeters (based on itaconic acid and N, N′-methylenebisacrylamide) when an X-ray irradiation dose from 0 to 300 Gy was applied. It was found that the best thermal stability of dosimeters prepared with modified gelatin would decrease the loss of information between the irradiation process and the absorbance reading, thereby improving the stability and linear correlation of data. °C and convenient reaction times for the preparation of the dosimeters. Subsequently, a mathematical model to easily predict the elastic modulus of materials prepared with different concentrations of gelatin and glutaraldehyde was proposed. The analytical response of modified and unmodified materials was evaluated and no significant alteration of the dosimetric sensitivity was found in the dosimeters (based on itaconic acid and N, N′-methylenebisacrylamide) when an X-ray irradiation dose from 0 to 300 Gy was applied. It was found that the best thermal stability of dosimeters prepared with modified gelatin would decrease the loss of information between the irradiation process and the absorbance reading, thereby improving the stability and linear correlation of data. Overall, the results indicated that the dosimeters could be modified as proposed and achieve significant improvements regarding to their thermal stability, without changing significantly the usual preparation process.